2019
DOI: 10.1371/journal.pone.0215443
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive electrochemiluminescence (ECL) immunoassays for detecting lipoarabinomannan (LAM) and ESAT-6 in urine and serum from tuberculosis patients

Abstract: Background Tuberculosis (TB) infection was responsible for an estimated 1.3 million deaths in 2017. Better diagnostic tools are urgently needed. We sought to determine whether accurate TB antigen detection in blood or urine has the potential to meet the WHO target product profiles for detection of active TB. Materials and methods We developed Electrochemiluminescence (ECL) immunoassays for Lipoarabinomannan (LAM) and ESAT-6 detection with detection limits in the pg/ml r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 49 publications
3
44
0
Order By: Relevance
“…FujiLAM's excellent performance in those with mycobacteraemia suggests a mechanistic association between disease dissemination and urinary LAM. This finding is supported by our recent study that showed a good association between detection of LAM in urine and serum of TB patients, independent of HIV status [15]. However, even for patients with forms of disease such as pleural TB and TB meningitis that may be compartmentalised, FujiLAM had moderate sensitivity, which could add substantial benefit in these cases.…”
supporting
confidence: 76%
“…FujiLAM's excellent performance in those with mycobacteraemia suggests a mechanistic association between disease dissemination and urinary LAM. This finding is supported by our recent study that showed a good association between detection of LAM in urine and serum of TB patients, independent of HIV status [15]. However, even for patients with forms of disease such as pleural TB and TB meningitis that may be compartmentalised, FujiLAM had moderate sensitivity, which could add substantial benefit in these cases.…”
supporting
confidence: 76%
“…Previous work from our team demonstrated the detection of urinary LAM at a maximal concentration of 350 pM in individuals without HIV co-infection using a sandwich immunoassay on an ultra-sensitive waveguide based optical biosensor [ 42 ]. The conclusions of this work are supported by a recent study using an improved chemiluminescence readout, with sensitivity and specificity of 93% and 97%, respectively [ 47 ]. These findings show that a more sensitive assay format is required in immunocompetent individuals.…”
Section: The Role Of “Omics” In Tb Diagnostic Developmentsupporting
confidence: 76%
“…However, LAM detection is not yet approved for use in diagnosis of HIV negative pediatric TB, likely because of the lower sensitivity of current diagnostic strategies. Researchers are working on the evaluation of the use of ultra-sensitive sensors in order to circumvent this problem [ 42 , 43 , 44 , 45 , 46 , 47 ]. The use of samples such as urine and blood favors application of this approach to children, and individuals with disseminated infection.…”
Section: Current Diagnostics For Pediatric Tbmentioning
confidence: 99%
“…There are few studies reporting LAM concentrations in clinical specimens and direct comparisons between different sample types and assays are complicated by the absence of standardized LAM control materials, sample panels, and reference assays. Four recent studies used the same purified LAM material for calibration and similar antibody reagents for immunoassay-based LAM detection (though different detection platforms) and reported LAM concentrations in sputum [33], blood [34,35], and urine [36] in subjects with active pulmonary TB, allowing for a rough comparison of LAM concentration ranges. For sputum, Kawasaki and colleagues showed that an immunoassay with a cut-off of 15 pg/mL detected all smear-positive and 50% of smear-negative TB patients [33] and sputum LAM concentrations ranged from 15.4 pg/mL to 1,869,000 pg/mL (median 5512 pg/mL).…”
Section: Lipoarabinomannan In Active Tb Diseasementioning
confidence: 99%
“…Serum LAM concentrations in this study were highest in HIV-positive/smear-positive patients (median 3.97 pg/mL). Broger and colleagues [34,36] developed sensitive immunoassays and compared serum LAM to urine LAM concentrations in matched samples from smear-positive TB patients. The serum assay detected LAM in 55% of smear-positive patients with concentrations of 6 pg/mL to 70,000 pg/mL but 45% of patients were below the cut-off of 6 pg/mL, suggesting a median concentration in serum of roughly 10 pg/mL.…”
Section: Lipoarabinomannan In Active Tb Diseasementioning
confidence: 99%